Mapping of rock resistivity value using geoelectrical method Schlumberger configuration in Solok Regency, West Sumatera - Elsi Ariani; Akmam Akmam (Journal of Physics: Theories and Applications, 2019)
Mapping of rock resistivity value is useful for knowing the potential of the natural wealth contained in the earth. Investigation of resistivity value in Solok Regency is using 3 lines. The first line is at S 00055'0.7 "and E 100040'56.8" coordinates, the second line is located at S 00054'53.2 "and E 100041'00.9" coordinates, and the third line is coordinated by S 00055'20.5 "and E 100041'01.8". The method of mapping is using the Geoelectric method with Schlumberger Configuration and the Ares (Apparent Resistivity) tool. The data obtained is processed by using Res2Dinv software to be analyzed and interpreted. The results obtained on the first line have resistivity value of 3.95-641 Ωm which is interpreted by having a rock structure consisting of Groundwater, Clay, Dry Clay, Basalt and Andesite. Next on the second line, the resistivity values of 2.53-1560.5 Ωm are obtained consisting of layers of rock Groundwater, Clay, Dry Clay, Basalt, and Andesite. Finally on the third line have resistivity value about 6.85-113.5 Ωm having a Groundwater, Tuff, Sandstone, Clay, Dry Clay, Basalt, Andesite, and Lava rock structure. The Tuff rock layer is estimated as a geothermal reservoir because its resistivity value is 20.8-23.6 Ωm surrounded by more contrasting rock layers and is located between two solid rock layers.